Optimization of tool geometry design for free cutting steel (AISI 12L14) in turning operation - Mohammad, Rosdi (2017)
The need for major improvements in the design of cutting tools are due to the demands of delivering high dimensional accuracy and low surface roughness products in turning operation. An optimization of cemented carbide (WC) tool geometry design for AISI 12L14 free cutting steel in turning process was carried out with the emphasis on the optimal workpiece through the quality of surface roughness. In this work, the performance of cutting inserts in the market and the newly developed cutting tools was investigated in terms of cutting forces and surface roughness (Ry). In the first phase, the selection of currently available cutting tools were done and modeled. Cutting forces simulation using AdvantEdge software was performed in determining the cutting tool-workpiece force interactions. In the second phase, the cutting tool-force interactions were studied and results revealed that tool geometry’s rake angle (γ) and cutting regimes such as depth of cut (ap) and feed rate (fr) gave significant impacts to the cutting forces (tangential force, radial force, and feed force) and Ry. A negative rake angle led to higher cutting forces compared to a positive rake angle. In third phase, a new proposed design of cutting tool was fabricated and tested according to rough and finish cutting conditions. Results showed that tool geometries of rake angle, inclination angle, and major (Kr1) and minor cutting tool’s angle (Kr2) had significant influences on cutting forces and Ry. In the fourth phase, the tool’s validation experiments were performed and the optimization was done by employing Taguchi method. The newly optimized tool cutter geometry was obtained at Kr1 of 60 and 90, Kr2 of +3, rake angle of +10, and the inclination angle of -3. It was revealed that ap and fr gave a significant impact on surface roughness. As ap and fr increased, Ry also increased except for setting parameters when ap was below than minimum chip thickness (Hmin). In the final phase, the performance of the newly developed cutting tool, in terms of Ry indicated that there was a significant difference between travel lengths and the progression of surface roughness correspond to tool wear or tool’s performance from 0 mm to 1560 mm (until tool breakage). However, none of the surface roughness results showed Ry more than 6.3. Additionally, cutting forces tend to increase with the increase of depth of cut (ap) when ap was higher than 1.15 mm. The feed force magnitude was almost similar to radial cutting force. However, the cutting force components started to deviate when the depth of cut was more than 1.15 mm whereby radial force slightly decreased with the increasing depth of cut. The effect of the combination of two cutting edges of the newly developed cutting tool could be the reason for radial force reduction. Hence, the newly developed tool was shown capable to produce final surface roughness within an acceptable range. The newly developed cutting tool demonstrated a great potential for turning operation market.